Estudio de la eficaicia del uso de broncodilatador inhalado versus nebulizado, en niños hospitalizados en el Área de Pediatría del Hospital Isidro Ayora, en edades de 6 meses a 3 años, periodo enero - junio de 2014. - Villa Rivera, Lourdes Marianela. (2015)
Bronchiolitis obliterans syndrome (BOS) is a disease characterized by inflammation, narrowing of the bronchial wall and hypersecretion of mucus that accumulates in the lumen hindering the passage of air. It manifests with coryza, cough, fever, wheezing, prolonged expiration, tachypnea and retractions. Often affects children under 3 years. The common risk factors: male gender, altered, prematurity and atopy immune response. This study compares the efficacy of inhaled nebulized salbutamol versus children aged 6 months to 3 years with SBO. 60 patients divided into 2 groups of 30 each method were selected. Being included variables: age, gender, hospital stay, clinical response, and adverse effects according to the method. It was evident that the SBO occurred more often in children under 24 months of age. As for the gender differences are not appreciated. The hospitalization was lower in children who received salbutamol with Aerochamber. Finally, patients using salbutamol with Aerochamber regained their normal clinical status earliest form, and with fewer adverse effects.